Gender Inequality and Education Attainment by Male and Female in Higher Institutions: A Case Study of Kabale University. - Twinomujuni, Promise (Kabale University, 2024)
The study was about the role of Gender inequality and education attainment by males and females in higher institutions. A case study of Kabale University Uganda. The objectives of the study were to examine factors for gender inequality in education attainment at Kabale University, to investigate the impacts of gender inequality on education at Kabale University, and to explore mechanisms to balance gender inequality in Education at Kabale University. The research used a case study design to address the research question depending on the characteristics of the study. A sample of 72 respondents was used, and data was collected using a questionnaire directed to administrators, lecturers, and students in the area. Data was analyzed using frequencies where percentages were derived for easy interpretation. Findings show that some respondents indicated that when individuals have their own family business, then they normally prefer that their children attain the educational qualifications, so they can provide assistance and support to their parents in augmenting their family business. From the findings, females with more than 7 years of education have on average, fewer children in Africa than women with no education, neutral about the statement. According to the results in the table above, addressing school and education system level of obstacles, feeding programs in schools was also highlighted as a strategy and change of negative socio-cultural. The study concludes that although women in Uganda today participate in higher education at much higher numbers, gender inequality remains a major factor in the country’s higher education system. Policies and measures that aim to tackle the growing nexus between pre-entry barriers faced by women in their transition from primary to higher levels of education; and entry barriers located at the points of entry in different colleges and ﬁelds of study are required. The study recommends that at the very least, there is a need now to review policies on educational equality between the sexes by taking note of the fact that it is not now women who are necessarily at a disadvantage, and also by paying attention to the achievement of boys. Advocate for policies that promote gender equality in education at all levels. Ensure that these policies are effectively implemented and monitored to bridge the gap in access to higher education for both genders. Tackle deep-rooted cultural norms and societal expectations that hinder girls' education. Educate communities about the importance of gender equality in education and empower girls to pursue higher education.